Case Report: Effects of multiple myeloma therapy on essential thrombocythemia and vice versa: a case of synchronous dual hematological malignancy - Krishnan, Nupur; Price, Russell; Kotchetkov, Rouslan (Frontiers in Oncology, 2023)
Background: Dual hematological malignancies, asynchronous or synchronous, are under-recognized entities and are usually suspected when clinical, hematological, or biochemical features cannot be explained by the primary malignancy alone. We present a case of synchronous dual hematological malignancies (SDHMs), where the patient was diagnosed with symptomatic multiple myeloma (MM) and Essential thrombocythemia (ET), when excessive thrombocytosis occurred following initiation of MPV (Melphalan-prednisone-bortezomib) anti-myeloma therapy. Case description: An 86-year-old female presented to the emergency in May 2016 with confusion, hypercalcemia, and acute kidney injury. She was diagnosed with FLC lambda and IgG lambda MM, and started melphalan–prednisone–bortezomib (standard of care at that time) treatment with darbopoietin support. At diagnosis, she has normal platelet count, since the ET was likely masked by bone marrow suppression due to active MM. After she reached stringent complete remission with no MP detected on serum protein electrophoresis or immunofixation we noticed her platelet counts increased to 1,518,000 x109/L. She was tested positive for mutation in exon 9 of Calreticulin. We concluded she has concomitant CALR positive ET. After bone marrow recovery from MM the ET became clinically apparent. We started hydroxyurea for ET. Treatment for MM with MPV did not affect the course of ET. Presence of concomitant ET did not decrease the efficacy of sequential anti-myeloma therapies in our elderly and frail patient. Conclusion: The possible mechanism underlying the occurrence of SDHMs is unclear but is likely due to stem cell differentiation defects. SDHMs can be challenging to treat and warrant several considerations. In the absence of clear guidelines on how to manage SDHMs, management decisions depend on several factors including disease aggressiveness, age, frailty, and co-morbidities.